2012
DOI: 10.1007/s00705-012-1490-9
|View full text |Cite
|
Sign up to set email alerts
|

Improved pig donor screening including newly identified variants of porcine endogenous retrovirus-C (PERV-C)

Abstract: Porcine endogenous retroviruses (PERV) are widely distributed in the genomes of pigs. PERV-A and PERV-B are present in all pigs. They infect human cells in vitro and therefore represent a risk for xenotransplantation when pig cells, tissues or organs are used. PERV-C infects only pig cells and is not present in the genomes of all pigs. However, PERV-A/C recombinants infecting human cells and characterized by high replication titers were found in pigs. To select PERV-C-free animals that cannot generate such rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…1). In addition, using primers and probes specific for PERV-C and for a recently described new variant of PERV-C, PERVCnv (Kaulitz et al, 2013), all animals were also found positive in a real-time PCR (data not shown), indicating that all known PERV subtypes are present in the genome of the pigs analysed in this study. Using a cloned PERV-C specific amplicon, the copy number of PERV-C was estimated: 45 copies/cell.…”
Section: Prevalence Of Pervs In the Donor Pigsmentioning
confidence: 76%
“…1). In addition, using primers and probes specific for PERV-C and for a recently described new variant of PERV-C, PERVCnv (Kaulitz et al, 2013), all animals were also found positive in a real-time PCR (data not shown), indicating that all known PERV subtypes are present in the genome of the pigs analysed in this study. Using a cloned PERV-C specific amplicon, the copy number of PERV-C was estimated: 45 copies/cell.…”
Section: Prevalence Of Pervs In the Donor Pigsmentioning
confidence: 76%
“…In theory, this can be used to eliminate the pig hepatocytes in favor of the human hepatocytes. The application of this approach was delayed over concerns about pig endogenous retrovirus [77].…”
Section: Engineered Intestinal Liver and Pancreas Regenerationmentioning
confidence: 99%
“…Such recombinant PERV-A/C are characterized by an increased replication competence compared with the parenteral virus [84][85][86][87]. Sensitive and specific methods have been developed to screen for PERV-Cpositive animals [88,89]. Third, RNA interference technology has been successfully used in transgenic pigs to reduce the expression of PERV in vitro [90][91][92] and in vivo [93][94][95].…”
Section: Microbiological Safetymentioning
confidence: 99%